Radiation-induced copper oxide formation in a clinical gel composite: a novel approach for dosimetry (Brazilian Journal of Radiation Sciences (BJRS), 2025)
This research is intended to investigate radiation-induced changes in a clinical gel composite with copper sulfate pentahydrate (CuSO₄·5H₂O). This study aimed to investigate the mechanisms was to understand the mechanisms of interaction between radiation and the material, within the proposal to develop accessible dosimetric materials that can efficiently monitor radiation doses. The samples were previously studied by ultraviolet-visible (UV-Vis) spectroscopy, demonstrating their potential for dosimetric use. For this work, the material was irradiated with gamma doses of 30 and 100 kGy and analyzed by nuclear magnetic resonance (NMR) spectroscopy and Raman spectroscopy. It was observed that the color of the samples changes from blue to red with increasing radiation dose, suggesting the formation of copper oxides. NMR analysis revealed changes in longitudinal (T1) and transverse (T2) relaxation times, indicating interactions between the gel matrix and copper sulfate. Raman spectroscopy confirmed the formation of new peaks associated with the presence of copper oxides. pH measurements were also performed to corroborate the results.